Generation Z Travel Planning: Analysis of Tourist Preferences in Adventure Tourism in Bali Province - Rahjasa, Putu Surya Laksana; Aspariyanthi, Ni Luh Putu Pradiayu; Rahadiarta, I Gede Ngurah Primanda S (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2023)
This study aims to analyze the travel preferences of generation Z in adventure tourism in Bali Province. Generation Z, which is a group born between 1995 to 2010, has unique travel preferences and is influenced by certain factors. This study uses survey methods and primary data collection from generation Z respondents who have visited Bali Province for adventure tourism purposes. The data collected includes travelers’ preferences regarding travel destinations, types of adventure activities of interest, desired comfort levels, sustainability priorities, and preferences for unique experiences. Data analysis was conducted using Preference Analysis and factor analysis techniques to identify patterns of traveler preferences. The results of this study show that generation Z tends to choose adventure tourism destinations that offer unique and memorable experiences. The results of this study provide valuable insights for tourism and destination managers in Bali Province. With a better understanding of generation Z's preferences, they can craft travel programs that better suit the needs and desires of this target market. This is expected to increase the attractiveness of Bali destinations as adventure tourism destinations for generation Z.